Von der Dienstleistung zur Marke: TUR-Raum-Führung, Patientenzeitschrift und After-Sales-Grüße im Wittener Marketingkonzept - Wiedemann, A.; Gellisch, O.; Abrolat, J.; Füsgen, I.; Heppner, Hans Jürgen (Aktuelle Urologie, 2015)
Marketing in economic systems means to create a brand in a competitive surrounding to serve customers as a target. Thereby, elements of marketing are product policy and pricing as well as distribution. Due to the fact that not only products and services are almost not modifiable at all and that price variation is impossible due to the DRG system but also common distribution channels, such as retail or wholesale, are prohibited, the fist mentioned marketing elements are of special importance. Primary customers are the referring physicians who are well served by medical education or presentations, which belong to the common facilities of a hospital department. Nowadays one can observe an increasing mobility of patients and an increasing willingness to inform themselves about medical topics and the service provider behind them. In conclusion, the maintenance of patients is a growing field for the economic success of a hospital or a hospital department. The marketing elements are ruled by the "Heilmittelwerbegesetz" and must fulfill the standards which are defined by this statute. Patient´s journals, a guided tour around the procedure rooms with technical equipment, an after-sales postcard and the participation in events not only with medical contents, such as fairs, can help to steadily establish an image, for example, as an ambitious and caring service provider.
CRIS-Team Scopus Importer:2022-09-26